The Effect Of Organizational Conflict On Organizational Commitment Through Job Satisfaction Among Managers of Village Economic Institutions - Saiful Anuar; Teuku Reza Kurniawan; Herman Herman; Jenita Jenita (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2026)
This study aimed to analyze the effect of organizational conflict on organizational commitment through job satisfaction among managers of Village Economic Institutions in Rokan Hulu Regency. This research employed a quantitative approach with an explanatory research design. The population consisted of managers of Village-Owned Enterprises (BUMDes), village cooperatives, and other village economic institutions. A sample of 180 respondents was selected using purposive sampling. Data were collected using a five-point Likert scale questionnaire and analyzed using JASP software through linear regression analysis and the Sobel test for mediation. Classical assumption tests included normality (Shapiro-Wilk), heteroscedasticity (Glejser), and multicollinearity (VIF). The results showed that organizational conflict had a negative and significant effect on job satisfaction (B = -0.631; p < 0.001). Organizational conflict also had a negative and significant effect on organizational commitment (B = -0.436; p < 0.001). Furthermore, job satisfaction had a positive and significant effect on organizational commitment (B = 0.709; p < 0.001). The mediation analysis using the Sobel test indicated that job satisfaction significantly mediated the relationship between organizational conflict and organizational commitment (Sobel z = 8.921; p < 0.001). This study confirmed that effective conflict management and efforts to enhance job satisfaction were important strategies for strengthening organizational commitment and improving the sustainability of village economic institutions. The findings contributed to Social Exchange Theory in the context of village economic institutions in Indonesia.